Epistemological and historical aspects of the anti-racist fight in Brazilian education - Nascimento , Sérgio Luís do; Alvarenga , Rodrigo; Lima, Cezar Bueno de (Argumentum, 2025)
Considering that the coloniality of power is impregnated in Brazilian schools and universities, institutionally reproducing racism, the aim of this article is to analyze the historical-normative process of resistance of the black movement for the anti-racist struggle through the epistemological disputes and tensions existing in the elaboration and implementation of educational policies. With an emphasis on Law 10.639, which made it compulsory to teach Afro-Brazilian history and culture in schools, it was possible to see that the law in question is an important milestone, but it is still far from achieving the reach and effectiveness needed to identify and make progress that, beyond hegemonic Western epistemologies in the field of education, makes it possible to confront and overcome racism and promote human rights.
Keywords: Decoloniality.; Human rights.; Education.; Racism.